Diffuse Intramuscular Lipomatosis of a Lower Limb. (1998) - Morris, Alfred D.; Jane, Mike J.; Ritchie, David; Helliwell, Tim
Abstract : Patient. A 40-year-old man presented with a swelling of the left thigh which had been increasing in size over 10 months. Surgery confirmed a diagnosis of lipoma. After 6 months, another swelling appeared, this time in the left calf. Ultrasound-guided biopsies revealed that the tissue showed appearances consistent with intramuscular lipoma. No further surgery was performed and the man is to be reviewed regularly, with possible debulking if necessary. Discussion. This case presents an atypical case of lipomatosis. Magnetic resonance imaging is useful for assessing the extent of the lesion.